Ecotourism and Cultural Production - Davidov, V. author. aut Link
XII, 267 p. 5 illus.
Keywords: Ecotourism is a unique facet of globalization, promising the possibility of reconciling the juggernaut of development with ecological/cultural conservation. Davidov offers a comparative analysis of the issue using a case study of indigenous Kichwa people of Ecuador and their interactions with globalization and transnational systems.